2019
DOI: 10.1093/synbio/ysz015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of primitive genetic interactions for the design of a genetic signal differentiator

Abstract: We study the dynamic and static input–output behavior of several primitive genetic interactions and their effect on the performance of a genetic signal differentiator. In a simplified design, several requirements for the linearity and time-scales of processes like transcription, translation and competitive promoter binding were introduced. By experimentally probing simple genetic constructs in a cell-free experimental environment and fitting semi-mechanistic models to these data, we show that some of these req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Recent efforts in this rather underexplored research area include the design of a differentiator module consisting of linear input/output functions realized by specific processes of protein production [14, 15]. It has further been demonstrated that calculation of time derivatives is possible by using ultrasensitive topologies operating within a negative feedback loop [16], and a motif capable of computing positive and negative temporal gradients, which includes input delays and the idea of an incoherent feed-forward loop, has been presented [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts in this rather underexplored research area include the design of a differentiator module consisting of linear input/output functions realized by specific processes of protein production [14, 15]. It has further been demonstrated that calculation of time derivatives is possible by using ultrasensitive topologies operating within a negative feedback loop [16], and a motif capable of computing positive and negative temporal gradients, which includes input delays and the idea of an incoherent feed-forward loop, has been presented [17].…”
Section: Introductionmentioning
confidence: 99%
“…BioSD modules can also be employed for derivative control, potentially in conjunction with proportional and integral action (PID control) [17]. Note that different approaches to realizing derivative action (including derivative control) via biochemical interactions have been proposed in the recent literature [12]- [16], [18], [20]- [22]. For a concise comparative discussion, we refer the reader to [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts in this rather underexplored research area include the design of a differentiator module consisting of linear input/output functions realized by specific processes of protein production ( Halter et al., 2017 ; Halter et al., 2019 ). It has further been demonstrated that calculation of time derivatives is possible by using ultrasensitive topologies operating within a negative feedback loop ( Samaniego et al., 2019 ), and a motif capable of computing positive and negative temporal gradients, which includes input delays and the idea of an incoherent feedforward loop, has been presented ( Samaniego et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%